Security Technology by using Firewall for Smart Grid - Ayla Hasanalizadeh Khosroshahi; Hossein Shahinzadeh (Institute of Advanced Engineering and Science, 2016)
Due to the increasing development of computer systems and information networks, power grids should change extensively too. Nowadays, substantial movement has begun to implement the Smart Grid industry around the world. Since with the creation of smart electricity grids, it is possible to access the internal network from the external spaces, it is also necessary to protect information and data against unauthorized access. Therefore, a firewall should be used for information security. The firewall based on existing security regulations, decides which data is incoming to the network or going out of the network. Considering the discussions of passive defense topics at the national level and also the high importance of information security in Smart Grids, in this paper, in addition to examining the Firewalls, its advantages and disadvantages are also stated. Although the firewall has a major role in establishing security, and its installation and appropriate configuration can only be one of the primary activities in this field, we should also take advantage of other security mechanisms to enhance the security of the Smart Grid.